The character of Imam Al-Bukhari from a psychological perspective - KHAIRUL NIZAM BIN ZAINAL BADRI (Pendidikan Agama Islam, 2022)
The study of positive psychology was first introduced by the American psychologist Seligman in the early 2000s. Included in this study is the role of parents in instilling positive emotions and character strength to children. In addition to parents, teachers also play a role in developing positive psychological behaviors, especially in terms of motivation. This study focuses on the research of Imam Al-Bukhari, a great figure in the field of hadith in the context of whether the family and the education system in his time has had a great influence on his character and psychological behavior to succeed as a leading figure in the field of hadith. This study found that the backbone of Imam Al-Bukhari’s success was due to the blessings and pleasure of his parents and teachers. This factor shows how important the spiritual element is in the field of psychology and it needs to be given attention in that field. As a conclusion, this qualitative pattern study successfully finds spiritual function, in triggering internal motivations that can be harnessed for the strengthening of positive character and emotions in the field of modern psychology.